PENGEMBANGAN MEDIA ULAR TANGA PADA PEMBELAJARAN PKN BERBASIS PROBLEM BASED LEARNING SISWA KELAS V SD NEGERI 33 LUBUKLINGGAU - Fadhilah, Farah; Valen, Andri; Firduansyah, Dedy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce Snakes and Ladders Media for PKN Learning Based on Problem Based Learning. Testing the validity, practicality and effectiveness of Snakes and Ladders Media in Problem Based Learning for Class V Students at SD Negeri 33 Lubuklinggau. This type of research is Research and Development with the ADDIE development model. The subjects of this research were 18 class IV students at SD Negeri 33 Lubuklinggau. Data collection techniques use questionnaires and tests. Based on the validation results of Ular Ladder Media based on the assessment of language 0,97 material 0,82 and media 0,81 experts, it shows that Ular Ladder Media meets the valid criteria. Meanwhile, from the analysis of teacher 83% student 88% and 90% practicality sheet assessments, it was found that Snakes and Ladders Media met the practical criteria. In the field test, an N-gain (g) of 0.74 was obtained with a high classification, which means that Snake and Ladder Media has high effectiveness. Based on the research results, it can be concluded that Snakes and Ladders Media has been proven to be valid, practical and effective in Problem Based Learning for Class V Students at SD Negeri 33 Lubuklinggau.   Keywords: development, elementary school, PKN, problem based learning, snakes and ladders media